Configuration paths of community cafe to enhance residents’ well-being: fsQCA analysis of 20 cases in Shanghai - Zhang, Man; Shen, Tao; Lou, Yongqi (Frontiers in Public Health, 2023)
Community cafes have emerged as a critical infrastructure for promoting communication and cultural construction in urban areas, and have gradually become an essential public place to enhance residents’ well-being. However, despite their growing importance, more empirical research is needed on the emerging concept of community cafes, including the configuration analysis of their influencing factors. To address this gap, this study employs the fuzzy set qualitative comparative analysis (fsQCA) method to examine 20 community cafes in Shanghai, China. The configuration effects on residents’ well-being are explored across five dimensions: activity quality, psychological cognition, physical quality, physical accessibility, and sociability. The findings reveal that sociability is necessary for high levels of residents’ well-being. Three configuration paths are identified to generate high well-being, which can be classified into activity-based or acquaintance-based social interaction patterns based on spatial functions. Additionally, the study identifies five groups of non-high well-being configurations, in which lack of activity quality and sociability are core conditions. Overall, the study contributes to evaluating community public spaces and provides insight into the configuration of factors that contribute to residents’ well-being. The study highlights that community public spaces can have significantly different impacts on residents’ well-being, with sociability emerging as a significant factor. Therefore, it is necessary to clarify community public spaces’ social orientation according to spatial conditions.